Propuesta de un nuevo esquema tecnológico para el procesamiento de polvos en ILE. - Godoy, Juan Carlos (2004)
The work present shows the study of the process of obtaining of the condiment "Sabora" and it proposes its substitution for a technological outline of continuous production, using the principle of haulage of particles, with the objective of eliminating the big powder emanations, the loss of materials, to humanize the work, to achieve the automation of the process and to diminish the energy consumption.